The Influence of Price and Taste on Consumer Preferences: A Study of Various Fried Chicken Outlets - Najwa Amirah; Muhammad Rizky Fahreza; Muhammad Daniel Haikal (Young Journal of Social Sciences and Humanities, 2025)
Abstract This study aims to examine the influence of price and taste on consumer preferences across various ayam geprek outlets. The increasing competition within the fast-food culinary sector, particularly among businesses offering spicy crushed fried chicken, has intensified the need to understand the determinants of consumer purchasing decisions. As consumer behavior becomes increasingly dynamic and value-oriented, identifying the key factors influencing outlet selection becomes essential for business competitiveness and sustainability. A quantitative research design was applied, using a structured questionnaire distributed to 120 respondents who had purchased ayam geprek from more than one outlet. The collected data were analyzed using multiple linear regression to determine both the partial and simultaneous effects of price and taste variables on consumer preferences. The findings indicate that price and taste each exert a significant influence on consumer preferences, demonstrating that both dimensions contribute meaningfully to decision-making patterns. Moreover, taste emerged as the most dominant determinant, suggesting that consumers prioritize flavor quality, consistency, and sensory satisfaction when selecting an outlet, while price functions as a complementary factor reflecting perceived value and product worthiness. These insights hold strategic implications for culinary business development and market positioning.